‘That Time of the Month’ – Investigating the Influence of the Menstrual Cycle and Oral Contraceptives on the Brain Using Magnetic Resonance Imaging - Schuster, Verena; Jansen, Andreas (Experimental and Clinical Endocrinology & Diabetes, 2022)
The stereotypic and oversimplified relationship between female sex hormones and undesirable behavior dates to the earliest days of human society, as already the ancient Greek word for the uterus, “hystera” indicated an aversive connection. Remaining and evolving throughout the centuries, transcending across cultures and various aspects of everyday life, its perception was only recently reframed. Contemporarily, the complex interaction of hormonal phases (i. e., the menstrual cycle), hormonal medication (i. e., oral contraceptives), women’s psychological well-being, and behavior is the subject of multifaceted and more reflected discussions. A driving force of this ongoing paradigm shift was the introduction of this highly interesting and important topic into the realm of scientific research. This refers to neuroscientific research as it enables a multimodal approach combining aspects of physiology, medicine, and psychology. Here a growing body of literature points towards significant alterations of both brain function, such as lateralization of cognitive functions, and structure, such as gray matter concentrations, due to fluctuations and changes in hormonal levels. This especially concerns female sex hormones. However, the more research is conducted within this field, the less reliable these observations and derived insights appear. This may be due to two particular factors: measurement inconsistencies and diverse hormonal phases accompanied by interindividual differences. The first factor refers to the prominent unreliability of one of the primarily utilized neuroscientific research instruments: functional magnetic resonance imaging (fMRI). This unreliability is seemingly present in paradigms and analyses, and their interplay, and is additionally affected by the second factor. In more detail, hormonal phases and levels further influence neuroscientific results obtained through fMRI as outcomes vary drastically across different cycle phases and medication. This resulting vast uncertainty thus tremendously hinders the further advancement of our understanding of how female sex hormones might alter brain structure and function and, ultimately, behavior.This review summarizes parts of the current state of research and outlines the essential requirements to further investigate and understand the female brain’s underlying physiological and anatomical features.
Keywords: sex hormones; brain structure; brain function; hemispheric lateralization; gray matter